In Silico Identification of Potential Inhibitors for Dengue Virus NS5 Methyltransferase: Molecular Docking, Dynamics, DFT, and ADME Analysis - Das B.; Pal P.C.; Upadhyay A.A. (My University, 2025)
Molecular dynamics (MD) simulations, confirmed the stablity of these inhibitor complexes under physiological conditions, with free energy landscape analysis further supporting their thermodynamic stability. Density functional theory (DFT) study revealed that CNP0019696 and the reference compound exhibited favorable electronic properties for strong binding interactions. Additionally, in silico ADME (absorption, distribution, metabolism, and excretion) analysis suggested favorable physicochemical properties, indicating good drug-like characteristics and bioavailability. Among the candidates, CNP0014493 and CNP0014756 emerged as the most promising, demonstrating significant potential as therapeutic agents for dengue treatment. These findings underscore the importance of targeting NS5-MTase in developing effective antiviral therapies and highlight the potential of phytocompounds in contributing to the global fight against DENG. © 2025 Wiley-VCH GmbH.